A Bisexual Perspective on Law School Hiring - Tweedy, Ann E. (Columbia Journal of Gender and Law, 2015)
There is still a significant amount of discrimination in the legal academy relating to many different issues, including race, gender, sex, sexuality, and class. The most overt discrimination that I have faced has been based on being bisexual. This has been exacerbated by the fact that some of my scholarship is about sexuality. In this short Article, I focus on discrimination in law school hiring based on bisexuality. The topic is important because discrimination against bisexuals in the legal academy (and elsewhere) is little understood and often invisible. Additionally, because it was the type of discrimination that was the most apparent to me in the hiring process, I have important insights to share about it. Furthermore, the invisibility and lack of understanding of bisexuality mean that even people who are broad-minded and committed to social justice may discriminate against bisexuals without realizing it.